Factors Influencing EFL University Students’ Willingness to Communicate: A Case of A Speaking Class - Johan Ariel Suwito Banunaek; Yohanis Nurak Siwa; Elvis Albertus Bin Toni (Journal of Applied Linguistics, 2026)
Willingness to Communicate (WTC) is an important aspect of English as a Foreign Language (EFL) learning because it determines students’ readiness to actively use English in classroom interaction. This study aimed to explore the factors influencing EFL university students’ willingness to communicate in English and to examine their perceptions and experiences of communicating in a speaking class. This research employed a qualitative case study design involving second-semester students of the English Education Study Program at Widya Mandira Catholic University Kupang. Data were collected through classroom observation of all students in two intact speaking class (N=50 students; Class A= 25 students and Class B= 25 students) and semi-structured interviews with ten purposively selected students (five students from each class). The data were analyzed using thematic analysis to identify recurring patterns related to students’ communication behavior, perceptions, and experiences. The findings revealed that students’ willingness to communicate was influenced by two major factors: psychological and situational factors. Psychological factors included self-confidence, anxiety, motivation, and personality, while situational factors included classroom environment, lecturer support, teaching strategies, learning activities, and peer interaction. Students were more willing to speak English when they felt supported, motivated, and emotionally safe in the classroom. However, fear of making mistakes, limited vocabulary, low confidence, and anxiety often reduced their willingness to participate. The study concludes that students’ WTC is dynamic and shaped by the interaction between internal emotions and external classroom conditions. Therefore, lecturers need to create supportive, interactive, and non-judgmental speaking environments to encourage students’ active participation in English communication. Keywords : Willingness to communicate; EFL students; speaking class; psychological factors; situational factors